Biomarkers in sarcoidosis: the contribution of system biology. Issue 5 (September 2016) - Carleo, Alfonso; Bennett, David; Rottoli, Paola
Abstract : Purpose of review: System biology is an interdisciplinary approach with the purpose to evaluate the experimental results of '-omics' sciences as a whole. The '-omics' sciences do not start generally from a-priori assumptions and are aimed to study the constituents of a specific biological domain (genome, transcriptome, proteome and metabolome) in a given state, using different high-throughput technologies (as polymerase chain reaction, arrays, liquid chromatography, mass spectrometry, etc.) and allowing a hermeneutical integration and recomposition of the experimental information. The aim of the present review is to explore the main new findings of system biology studies applied to sarcoidosis in the last year. Recent findings: The main new findings of sarcoidosis that were highlighted by different studies in the last year (including miRNAs, TGF-β pathway, TNF-α and related proteins, vesicle trafficking, vitamin D and lipid metabolism, analyzed by system biology) are presented in this article. Summary: System biology is a useful approach to combine different experimental results to study the pathogenesis of sarcoidosis and to identify groups of new molecules and mediators with potential clinical application as biomarkers.